2006
DOI: 10.1177/1082013206063735
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Fresh-cut Mangoes Prepared from Fruit Sanitised in Hot Chlorinated Water

Abstract: Whole mangoes (Mangifera indica, cv. Chok Anun) were washed in water with or without chlorine (100 mg total chlorine/L) at 11.7 ºC and 50 ºC before slicing and packaging. Microbiological analysis of the whole fruit showed that the stem scar contained larger populations of microorganisms than the skin. Washing reduced populations at both sites and the effect was enhanced by the addition of chlorine and heating of the wash water. None of the treatments prevented transfer of contaminants to the flesh during slici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
7
0
5
Order By: Relevance
“…After 1 day of storage, HWD samples had lower mould and yeast populations than the others. This result could be explained by the results of Ngarmsak et al. (2006) which indicated that mild heat treatments applied at 50 °C for 5 min on mango fruit reduced the risk of contamination of the flesh during processing.…”
Section: Resultsmentioning
confidence: 94%
“…After 1 day of storage, HWD samples had lower mould and yeast populations than the others. This result could be explained by the results of Ngarmsak et al. (2006) which indicated that mild heat treatments applied at 50 °C for 5 min on mango fruit reduced the risk of contamination of the flesh during processing.…”
Section: Resultsmentioning
confidence: 94%
“…Esses resultados estão de acordo com Ngarmsak et al (2006) os quais observaram que fatias de mangas preparadas a partir de frutos sem sanificação apresentaram maior nível de microrganismos em relação às fatias provenientes de frutos sanificados em água (11,7ºC), com 100 mg.L -1 de cloro ou provenientes de frutos imersos em água a 50ºC por cinco minutos com ou sem 100 mg.L -1 de cloro. Tanto o cloro quanto a água quente interferem no crescimento microbiano.…”
Section: (Recebido Em 23 De Janeiro De 2007 E Aprovado Em 30 De Julhounclassified
“…Quanto à utilização de água quente, essa pode causar injúrias aos microrganismos e inabilitar a recuperação do estresse adquirido durante o tratamento (NGARMSAK et al, 2006). Sertthikul et al (2003), citados por Ngarmsak et al (2006) observaram que a imersão a 60ºC por 20 minutos ou 62ºC por quatro minutos eliminou 86% da Salmonella entérica spp inoculada em manga. Diante desse fato, pode-se inferir que, no presente trabalho, a imersão dos frutos sanificados em água a 50ºC por oito minutos contribuiu para potencializar a redução da carga inicial de microrganismos.…”
Section: (Recebido Em 23 De Janeiro De 2007 E Aprovado Em 30 De Julhounclassified
“…Washing with chlorinated water is a widely employed sanitation procedure accomplished by immersing the product in solutions containing between 50 and 200 µL/L free chlorine (HOCl) during less than 5 min (Ngarmsak et al, 2006;Rico et al, 2007). Even though the application of chlorine is not considered very effective in reducing microbial levels in contaminated tissue, chlorine reduces microbial loads in the water and prevents cross-contamination.…”
Section: Sanitation Treatments Prior Processingmentioning
confidence: 99%
“…Chlorine dioxide (ClO 2 ), a strong oxidizing and sanitizing agent, has a broad and high biocidal effectiveness and is also less affected than chlorine by pH and organic matter (Zhang, 2007). Hydrogen peroxide (H 2 O 2 ), acidified sodium chloride, peroxyacetic acid, and organic acids have also been used to sanitize fresh-cut fruits and vegetables (Brecht et al, 2004;Narciso and Plotto, 2005;Ngarmsak et al, 2006;Rico et al, 2007). Peroxyacetic acid (PAA) is currently the most commonly used sanitizer in commercial fresh-cut processing facilities.…”
Section: Sanitation Treatments Prior Processingmentioning
confidence: 99%